Pressure mapping and susceptibility to bonding failure for low-quality lamstock in cross laminated timber - Dalisson Peterson Silva do Carmo; Karl Englund; Hui Li (Case Studies in Construction Materials, 2023)
Cross Laminated Timber (CLT) is thriving as a wood engineered material across the globe. As demand increases, lamstock solutions become necessary to supply the demand, and low-quality lumber has been pointed as an option to solve this problem. Nevertheless, low-quality lumber has significant warping that spreads skepticism towards bonding failure due to out-of-plane defects. This article aims to investigate bonding failure using a pressure mapping, built with a Pressure Prediction Model, comparing theoretical results with block shear and cyclic delamination tests observations. Block shear test indicates no significant difference of wood failure results among different pressures zones using 2-ply lamination samples with a manufacturing press of 414 kPa. Cyclic delamination occurred in an insignificant frequency for samples in all pressure zones analyzed. In summary, for this study, the bonding strength could resist the residual stresses caused by warping experimentally. The findings of this investigation can encourage CLT manufacturers to utilize undervalued and low-grade materials such as small diameter timber (SDT) as a feedstock and contribute to the sustainability of CLT market growth.